Inhibitory Effect of Alternanthera Sessilis, Cucurbita Maxima and Aerva Lanata on Whewellite Urinary Crystals - Sabitha, M. A.; Mohamed, Syed (جامعة الملك فيصل, 2024)
Phosphate stones, such as struvite (magnesium ammonium phosphate hexahydrate), brushite (calcium hydrogen phosphate dihydrate), and oxalates like whewellite (calcium oxalate monohydrate) are different kinds of urinary stones. Such kidney stones can be treated with herbs for natural healing and side effectsfree results. These urinary crystals are traditionally created in the lab using the gel growth process and a silica gel medium at a specified pH. The inhibitory effects can be analysed by using the extracts of herbal plants. In the present study, ethanol extracts of leaves of Alternanthera sessilis, seeds of Cucurbita maxima and flowers of Aerva lanata are investigated for their inhibitory activity against the whewellite urinary crystals. They are characterized using Fourier transform infrared spectrum and their crystalline nature is examined through powder X-ray diffraction. Asymmetric and symmetric stretching unit of C=O in oxalate appears at 1620 cm-1 and 1400, 1310 cm-1 respectively. The monoclinic crystal system with a space group of P21/n is confirmed from the powder X-ray diffraction studies. The results indicated that among the three ethanol extracts, leaves of Alternanthera sessilis, seeds of Cucurbita maxima and flowers of Aerva lanata- the flowers of Aerva lanata exhibited inhibition towards whewellite crystals.
Keywords: حصوات الكلي -- النباتات العشبية -- الأشعة تحت الحمراء